2016
DOI: 10.1080/00015458.2016.1156929
|View full text |Cite
|
Sign up to set email alerts
|

Chronic kidney disease as major determinant of the renal risk related to on-pump cardiac surgery: a single-center cohort study

Abstract: On-pump CSA-AKI was observed in nearly 15% of cases and was associated with poorer outcomes. Interestingly, the risk of CSA-AKI could be estimated preoperatively, thanks to the basal renal function, which exhibited an equal performance to the STS score.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 28 publications
0
6
0
Order By: Relevance
“…As previously described, patients with preoperative renal dysfunction are at an increased risk of developing postoperative AKI 19, 27 , even those patients who exhibit proteinuria without an observed decrease in eGFR 28, 29 . Given the increased mortality and morbidity associated with CKD and AKI independently, these effects of these complications are worse when they occur together 6, 7, 14 .…”
Section: Outcomes - Mortalitymentioning
confidence: 77%
“…As previously described, patients with preoperative renal dysfunction are at an increased risk of developing postoperative AKI 19, 27 , even those patients who exhibit proteinuria without an observed decrease in eGFR 28, 29 . Given the increased mortality and morbidity associated with CKD and AKI independently, these effects of these complications are worse when they occur together 6, 7, 14 .…”
Section: Outcomes - Mortalitymentioning
confidence: 77%
“…Upon reviewing previous studies, we found that 5 papers had the same study outcome as ours. By studying 252 patients undergoing cardiac surgery under cardiopulmonary bypass, Jean-Michel Hougardy et al found that baseline renal function can predict postoperative acute kidney injury and poor prognosis (15). Pablo Jorge Monjas and others found that renal function can be used as an important predictor of postoperative acute kidney injury.…”
Section: Discussionmentioning
confidence: 99%
“…We have [13] patients in the pump group [43%] Vs. [3] patients in the off-pump group [10%] who had impaired postoperative kidney functions. In the on-pump group, there were [9] patients who required dialysis [30%], and they were among the group of [13] patients who were diagnosed as postoperative renal dysfunction, while in the offpump group [2] patients required dialysis [6.76%] and they were among the [3] patients who had postoperative renal dysfunction. Comparing that to other studies as following Mahmoud et al [8] that shows [27%] of patients in pump group who had impaired postoperative renal dysfunction and [7%] of those had needed renal dialysis while in the offpump group [6%] of patients had impaired postoperative renal functions and [2.3%] of those needed hemodialysis and also Arslan et al [20] that shows [18.75 %] of patients in the pump group who needed renal dialysis while in the off-pump group [2.77%] only needed renal dialysis.…”
Section: Discussionmentioning
confidence: 99%
“…Coronary artery bypass grafting [CABG] performed using cardiopulmonary bypass [CPB] has been the ideal treatment for patients with ischemic heart disease. However, there has been increasing evidence that CPB may be responsible for part of the morbidity associated with CABG surgery [2] .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation